Caries risk and prevention: Evaluation of a preventive program in a clinic for children - Fábio Correia Sampaio; Franklin Delano Soares Forte; Andréa Cristina Barbosa da Silva; Júlia Magalhães da Costa Lima (Faculdade São Leopoldo Mandic, 2008)
Objective: The aim of this study was to verify the use of the Nexø caries risk assessment system together with the Cariogram® (School of Dentistry, Malmö, Sweden), in a preventive program for children at the cariology clinic at Federal University of Paraíba. Methods: A sample of 107 children (2- to 14-year-old) was attended on two occasions. The patients' clinical data (DMF-T, dmf-t, Bleeding index, OHI-S) and those from the preventive procedures performed (professional cleaning, fluoride application, Cariogram® (School of Dentistry, Malmö, Sweden), Nexø caries risk) were collected twice: first from the clinical record cards and on the second occasion by exams. Parents and guardians evaluated the clinical attendance in an interview and the children, by means of a VAS scale. According to the Nexø caries risk assessment system, 53 children (49.5%) were classified at low risk (<5) and 54 children (50.5%) at high risk (>6). Data analysis was carried out using SPSS (11.0). Results: A positive correlation was observed between the two risk systems: Nexø and Cariogram® (School of Dentistry, Malmö, Sweden) of chances of avoiding new caries lesions). The possibility of avoiding new caries lesions increased 5% in both groups and a discrete increase was observed in the other parameters. Conclusion: It can be concluded that the Nexø system associated with the Cariogram® (School of Dentistry, Malmö, Sweden), contributed to the assessment of the patients' caries risk profile and to the success of the preventive program for children at the cariology clinic at Universidade Federal da Paraíba.